Electrochemical coding for multiplexed immunoassays of biomarkers based on bio-based polymer-nanotags. (1st May 2015) - Wang, De; Li, Tianhua; Gan, Ning; Zhang, Huairong; Long, Nengbing; Hu, Futao; Cao, Yuting; Jiang, Qianli; Jiang, Shan
Graphical abstract: Highlights: Electrochemical coding for multiplexed immunoassays was designed for simultaneous detection of biomarkers. Encoded polymer-nanotags were developed for signal amplification based on Apo nanotags modified on PLL-Au composite. Apo nanoparticles with a high coding capacity with cadmium and lead ions were used as distinguishable tracer labels. The polymer-nanotags were simply prepared and environment-friendly by self-assemble technology without coupling agents. Abstract: A novel sandwich-type electrochemical multiplexed immunoassay was designed for simultaneous determination of alpha-fetoprotein (AFP) and carcinoembryonic antigen (CEA) cancer biomarkers by using bio-based polymer-nanotags as signal probes and dual antibodies labeled magnetic beads as capture probes. This signal probes were prepared by co-immobilizing encoded metallic apoferritin (Cd-Apo and Pb-Apo) and primary antibodies (anti-AFP and anti-CEA) on poly-L-lysine (PLL) via gold nanoparticles (AuNPs). The preparation procedures were through self-assembly technology without using coupling agent. After a sandwich-type immunoreaction, the polymer-nanotags were captured to the surface of Dynabeads. The subsequent electrochemical stripping analysis of the metal components from the nanocomposite provide a means for discriminating dual targets based on the peak potential of Cd and Pb. The currents of Cd and Pb were proportional to the concentration of AFP and CEA, respectively. Experimental results showed the immunoassay enabled the simultaneous determination of AFP and CEA in a single run with dynamic ranges of 0.01-50 ng mL −1 . And the detection limits of AFP and CEA were 4 pg mL −1 (S/N = 3), respectively. This proposed multiplexed immunoassay is simple, sensitive and environment-friendly. More importantly, this proposal was employed in real serum samples to detect two tumor markers at the same time. It can be applied for clinical screening of biomarkers.